The paradoxical availability of raw materials in the bioethanol production = La paradójica disponibilidad de materia prima en la producción de bioetanol - Cirilo, Nolasco-Hipolito; Octavio, Carvajal-Zarrabal; Kopli, Bujang; Cynthia Magaly, AntonioCisneros; Jesús, Carrillo-Ahumada; Ibrahim, Yakub; María de Jesús, García-Gómez; Óscar, Núñez-Gaona (Universidad Autónoma de Chihuahua (UACH), 2023)
The production of bioethanol is influenced by economic, social, political, and technological aspects. Technology has contributed to improving and simplifying the production process. On the other hand, the global pandemic of SARS-CoV-2, better known as Covid-19, has affected the market as its price has substantially increased. Raw material and transportation costs have also impacted the international market. Therefore, more efforts are being dedicated to finding alternative raw materials for bioethanol production. Agricultural waste or starches that are not used entirely for human consumption have the potential to produce bioethanol, but paradoxically, they cannot be commercialized. This report focuses on potential raw materials for bioethanol production and how their possible commercial exploitation declines when they acquire a cost for their transformation into higher value-added products. Price increases discourage investment in the diversification of these raw materials.